Investigating the Integration Level of Information and Communication Technology (ICT) in the English Language Teaching - Rija Dwiono; Dewi Rochsantiningsih; Suparno Suparno (Universitas Jambi, Magister Program of English Education Department, 2018)
Information and Communication Technology (ICT) is perceived as a part of the core of education in this 21st century-learning. Experts have explored the integration of pedagogical ICT in teaching and learning recently. But none of them explored the teacher’s competence to integrate pedagogical ICT as they assess the extent to which ICT integrated by the teacher in teaching. This research aims to investigate the teacher competence levels to use ICT and the extent to which the ICT integrated by the teacher in English language teaching. Classroom observation and interview were used as data collecting technique to reach the objectives. To produce an in-depth description, this case study focuses on the description of the individual teacher as the target of the investigation. Teacher’s ICT competence levels were classified using professional framework rank ICT competence level (UNESCO, 2011). While SAMR model was used as the data analysis tool to determine the extent to which ICT integrated by the teacher in the English language teaching. The results of this research indicate that the teacher's competence to use ICT was still beginner. It means that the teacher is dominant with the use of basic features of presentation, word processor software such as powerpoint and Microsoft word and other digital resources. It is also reported that teacher’s ICT integration level with the domination at the substitution level and augmentation level. These findings reflect the ability of the teacher in integrating ICT in teaching. The teacher is considered only be able to use basic function in a limited number of computer application with only little change and improvement.